Baseline Myelopathic Severity is an Independent Determinant of Adverse Outcomes, Complications and Functional Recovery Following Adult Cervical Deformity Corrective Surgery. (16th November 2020) - Passias, Peter; Pierce, Katherine; Ahmad, Waleed; Naessig, Sara; Diebo, Bassel G
Abstract: INTRODUCTION: Little is known of the impact of myelopathy severity in patients undergoing cervical deformity (CD) on postoperative patient-reported outcomes when taking into account neck disability severity and symptomatic presentation. METHODS: Surgical CD patients with baseline HRQLs and radiographic follow-up[1-yr]. mJOA assessed baseline myelopathy severity, Tetreault et al.(Severe <12). Ratios of baseline myelopathy groups to neck disability groups(Vernon et. al:), assessed myelopathy in conjunction with neck disability. A ratio >1 indicated that myelopathy severity weighed more than neck disability, and vice versa. In a subanalysis, Severe and Not Severe myelopathy groups were PSM for cSVA. Univariate analyses were performed to determine whether myelopathy severity impacted postop outcomes. RESULTS: 136 CD patients included(56.6yrs, 49%F, 29.9kg/m 2 ). Baseline mJOA: 13.1 ± 2.9, NDI of 58.9 ± 18.8. 28.7% had Severe baseline myelopathy, 71.3% Not Severe. Severe patients had greater baseline NDI scores (68.2 vs Not Severe: 55.1, P  < .001). Patients more impacted by myelopathy had greater postop neurological complications (25%, vs greater NDI:3%, P  = .042) and DJK(25%), P  = .034. After PSM for cSVA in the subanalysis, 26 patients remained in Severe and Not Severe myelopathy groups. Severe had increased neuro complications(15.4%) and met MCID for EQ5D significantly less than the Not Severe baseline myelopathy patients (11.5% vs 34.6%), both P  < .05. From baseline to 1-year, 31.5% improved, 49.3% same, and 19.2% deteriorated in their myelopathy severity. Patients who improved in mJOA severity by 1-yr had less incidence of DJK (0% vs 8.3 vs 28.6) CONCLUSION: Patients who report more severe myelopathy over neck disability preoperatively are at increased risk for neurologic complications and distal junctional kyphosis occurrence. When controlling for baseline deformity severity, this remained true for patients with severe myelopathy presentation along with decreased overall quality of life at follow up.